2005
DOI: 10.1080/13685530500298154
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between testosterone serum levels and lifestyle in aging men

Abstract: Objective. The aim of this study was to evaluate the association between serum levels of testosterone and free testosterone to lifestyle in aging males. Methods. Men between 45 and 85 years were assessed regarding body mass index (BMI), nicotine and alcohol consumption, stress level, physical and social activity, and sleeping quality by a self-administered questionnaire. In parallel, serum levels of testosterone (T), free testosterone (fT), LH, FSH, DHEA-S, E2 and SHBG were obtained. Results. In total, 375 men… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
21
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 21 publications
6
21
0
Order By: Relevance
“…Increasing age was by far the strongest factor associated with low BT, consistent with other reports that age‐related decreases in BT are greater than those observed for TT 12,15 . Similarly, smoking has previously been reported to be associated with an increased BT 15,19,21,23,54,55 . BMI has previously been shown to be inversely associated with BT 55 and we demonstrate that this is also the case with whole body fat, but not abdominal fat suggesting that the additional effect of abdominal fat on TT is mediated by the effect of abdominal fat on SHBG.…”
Section: Discussionsupporting
confidence: 91%
“…Increasing age was by far the strongest factor associated with low BT, consistent with other reports that age‐related decreases in BT are greater than those observed for TT 12,15 . Similarly, smoking has previously been reported to be associated with an increased BT 15,19,21,23,54,55 . BMI has previously been shown to be inversely associated with BT 55 and we demonstrate that this is also the case with whole body fat, but not abdominal fat suggesting that the additional effect of abdominal fat on TT is mediated by the effect of abdominal fat on SHBG.…”
Section: Discussionsupporting
confidence: 91%
“…In men, an increase in LH was observed only in connection with smoking high-nicotine cigarettes, while there were no changes in testosterone levels with either high-nicotine or low-nicotine cigarette smoking (30). However, another study reported higher levels of testosterone and free testosterone in male smokers (31).…”
Section: Discussionmentioning
confidence: 95%
“…At present, the relationship between physical activity levels and male sex steroid hormone levels remains unclear. Some cross-sectional studies have found greater amounts of habitual physical activity to be associated with higher testosterone levels (Shiels et al 2009; Muller et al 2003; Ari et al 2004; Allen et al 2002; Goh et al 2007; Mantzoros and Georgiadis 1995; Yeap et al 2009), while others show no association between physical activity and testosterone levels (Allen et al 2002; Handa et al 1997; Lindholm et al 1982; Dai et al 1981; Ponholzer et al 2005; Camacho et al 2013). Physical activity intervention studies have also yielded inconsistent findings regarding the relationship between physical activity and testosterone levels (White et al 2002; Hall et al 1999; Hawkins et al 2008; Heufelder et al 2009).…”
Section: Background and Significancementioning
confidence: 99%